P08 Automated calculation of the RV:LV ratio in acute pulmonary embolism: a real-world feasibility and clinical impact study. (7th September 2020) - Foley, R; Glenn-Cox, S; Hudson, B; MacKenzie-Ross, R; Suntharalingam, J; Robinson, G; Rodrigues, J
Abstract : Introduction: The right ventricle to left ventricle (RV:LV) ratio >1 on CT pulmonary angiography (CTPA) is the most important predictor of adverse outcomes in acute pulmonary embolism (PE). The 2019 National Confidential Enquiry into Patient Outcome and Death for PE demonstrates that this metric is poorly reported. We assess the feasibility of an entirely automated RV:LV analysis and determine its clinical impact in a real-world setting. Methods: 101 consecutive patients with CTPA-proven acute PE (April 2019 to August 2019) were retrospectively analysed with automated post-processing software (Imbio, USA). RV and LV volumes were segmented on 1.5 mm contrast-enhanced axial slices and maximal ventricular diameters were derived for RV:LV ratio. Clinical reports were reviewed for mention of right heart strain. The automated RV:LV ratio was compared with clinical reports to determine how this would have altered practice if it has been available at the time of the report. Results: Entirely automated RV:LV analysis was feasible in 87% (n=88). RV:LV ratios ranged from 0.67–2.43, with 64% (n=65) >1.0. Terms implying RV strain were mentioned in 66% (67/101) but RV/LV ratio itself was provided in 4% (4/101). Where RV:LV was >1.0, right heart strain was mentioned in 46% (n=30/65) clinical reports. Automated RV:LV ratio would have added important prognostic information in 54% (n=35/65). Conclusion: In a real-word setting of acute PE, automated RV:LV analysis is reliable when LV intraventricular attenuation >100HU. Applied routinely, this technology would improve risk stratification in the majority.